Impacts of export-platform FDI on backward linkages - Do third country size, trade agreements and heterogeneity of firms matter? Evidence from the Vietnamese supporting industries - Thanh Tam Nguyen-Huu; Minh Nguyen-Khac (Kiel Institute for the World Economy (IfW), 2017)
The paper investigates the impacts of export-platform foreign direct investment (FDI) on backward linkages. First, in a three-country model, these impacts are explained through the competition effect and the demand effect. Whenever the former is stronger than the latter, the investment has a negative impact on the level of backward linkages and conversely. Otherwise, the level of backward linkages is also affected by third country size, local content requirement, and the power of trade agreements between the host and the third countries. Second, in the case of the Vietnamese supporting industries between 2000 and 2012, export-platform FDI generates a negative effect. Moreover, local content requirement, and trade agreements between Vietnam and third countries (bilateral trade agreement with the U.S. and entry of Vietnam into the WTO) positively impact the level of backward linkages whereas third country size has an ambiguous impact.
Keywords: F15; F23; O1; 330; export-platform FDI; backward linkages; local content requirement; third country size; power of trade agreements; Vietnam